ANALISIS MANAJEMEN SUMBER DAYA MANUSIA PADA PENDIDIK DAN TENAGA KEPENDIDIKAN DI MA AL MA’ARIF SERUPA INDAH PAKUAN RATU KABUPATEN WAY KANAN - Tuti Widayati; Suci Hartati (UNISAN JURNAL, 2022)
The abstract submitted to Tuti: Jurnal Manajemen Pendidikan Islam, Many madrasas are in the public spotlight regarding the quality of human resources for educators and education personnel, this is because in addition to the large number of them, the quality of the management of educators and education staff has so far not been able to align with other general education. However, madrasa institutions need to implement strategies, one of which is the continuous implementation of Planning, Organizing, Actuating, Controlling educators and education personnel. Queen of Way Kanan Regency. Organizing with placements that are regulated directly by the Chair of the Foundation and the Head of Madrasah. Physical and non-physical movement through training is carried out periodically and controlled by the application of good discipline and dismissal is carried out if the discipline violates repeatedly. comparison of the management of Educator Recruitment Planning, Organizing the Placement of Educators and Educational Staff, Mobilizing Educators and Educational Personnel, and Management The most important subjects in this study are the headmaster, teachers, madrasa committee of the two schools, have many similarities and differences. differences in several aspects are therefore mandatory to improve the quality of madrasas and are expected to become treasures and inputs for madrasas.